SAT0105 Circulating MIR-223 is downregulated in SERA of patients with early RA after treatment with methotrexate. (23rd January 2014) - Filkova, M.; Ospelt, C.; Šenolt, L.; Vettori, S.; Mann, H.; Michel, B.A.; Vencovský, J.; Pavelka, K.; Gay, R.E.; Gay, S.; Jüngel, A.
Abstract : Background: MiRs are involved as fine tuning regulators of gene expression in crucial cellular processes and their dysregulation has been described in many diseases. Incorporated in microvesicles, in complexes with Ago2 or high density lipoproteins, miRs show high stability in body fluids. Therefore, studying circulating miRs as potential biomarkers is of big interest. Objectives: To analyze the profile of circulating miRs known to be associated with the pathogenesis of rheumatoid arthritis (RA) before and after treatment in patients with early RA (ERA) and established RA, their association with clinical activity and response to therapy. Methods: Treatment naïve patients with ERA (n=42, median disease duration 3 months, 59.52% RF+, 47.61% ACPA+), fulfilling 2010 ACR/EULAR classification criteria for RA, who started therapy with methotrexate (MTX) and active patients with established RA (n=17, 76.47% RF+, 52.94% ACPA+), fulfilling 1987 ACR criteria, who were treated with TNFα blockers (Adalimumab, n=6; Infliximab, n=6; Etanercept, n=5) were included in this study. Sera/plasma were obtained before and 3 months after initiation of treatment. Total RNA was isolated by phenol-chloroform extraction and miRs were reverse transcribed using specific primers with equal input of 12.5ng RNA. The expression of miR-124a, 132, 146a, 155 and 223 were analyzed by TaqMan Real-Time PCR. MiR-let7a was used as an endogenous control. Data were calculated with dCt method. Results: In ERA sera, miR-223 significantly decreased following the treatment with MTX (p=0.002), while levels of miR-132, 146a and 155 did not change. Expression of miR-223 positively correlated with DAS28 (p=0.022), CRP (p=0.010) and the number of leukocytes before (p=0.004) and after treatment (p=0.007). MiR-146a and 155 showed no association with disease activity at baseline or after MTX treatment. The baseline expression of miR-132 and 155 was higher (p=0.05) in patients with good (n=22) compared to moderate (n=11) clinical response to therapy but did not significantly differ from non-responders (n=4). In plasma of patients with established RA, the expression of miR-132, 146a, 155 and 223 did not correlate with DAS or CRP at baseline or after treatment. The expression of these miRs was not affected by TNFα blocking therapy and was comparable in responders or non-responders prior treatment. MiR-124a was not detectable in any of the samples. Conclusions: MiR-223 correlated with the disease activity in treatment naïve patients with early RA and was significantly downregulated after MTX. MiR-223 is known to be overexpressed in T-lymphocytes of RA patients (Sebastini GD et al. 2011) and its presence in circulation may reflect pathogenic mechanisms in RA. We hypothesize that the expression of circulating miRs might serve as a potential tool to monitor disease activity and response to treatment, particularly in early stages of the disease. Acknowledgement: This work was supported by IMI BTCure, IAR Epalinges, project No. 00023728 and MH CR-grant project No.10065-4. Disclosure of Interest: None Declared